EXERGY ANALYSIS OF THE ORGANIC RANKINE CYCLE BASED ON THE PINCH POINT TEMPERATURE DIFFERENCE - Bademlioğlu, Ali Hüsnü; Yamankaradeniz, R.; Kaynakli, O. (Yildiz Technical Univ, 2019)
Organic Rankine Cycle (ORC) is a system that uses working fluids with hydrocarbon components instead of water and generates power from the heat recovery of different heat sources. In this study, the exergy analysis of a simple ORC, which produces electrical energy with the help a geothermal source (125 degrees C), was performed. R123, R152a, R245fa and R600a were determined as the fluids to be used in the Cycle. In this analysis, which was carried out according to the pinch point temperature differences (5-20 degrees C) in the evaporator, the exergy performance of the cycle components was evaluated for the geothermal resource unit flow rate and the variation of the exergy efficiency of the system was calculated. With the increase of the pinch point temperature difference in the evaporator, the decrease of the system's exergy efficiency became maximal (11.7%) with the use of R152a as a refrigerant and the loss in the system's exergy efficiency became minimal (9.03%) with the use of R123 as a refrigerant.
Keywords: Organic Rankine Cycle; Exergy Analysis; Pinch Point Temperature; Refrigerant; Geothermal Source